To answer this question, you need to draw out the graph first. By doing so, you will be able to know where the other endpoint is located. (Fig. 1)
Next, count the number from the midpoint to the endpoint to determine the coordinates for the other endpoint. (Fig. 2)
Example: From (2, 5) to (6, 3)
x: 2 to 6 = 4 steps
y: 5 to 3 = 2 steps
From there, you can determine the other endpoint like this.
Example: From (2, 5) to the other endpoint
x: 2 to x1 = 4 steps
y: 5 to y1 = 2 steps
Therefore, x1 = -2 and y1 = 7
Other endpoint: (-2, 7)
Sorry for the messy drawing, it is hard to draw without a pen. Haha... hope this helps :)
Answer:
x/6 + 3 = 8
x/6 = 5
x = 30
Step-by-step explanation:
The answer would be .0333 hope this helped
Answer:
3b - 2 = 4
Step-by-step explanation:
3(2) = 6
6 - 2 = 4